Electrochemical N-acylation synthesis of amides under aqueous conditions. Issue 16 (26th July 2019) - Ke, Fang; Xu, Yiwen; Zhu, Suning; Lin, Xiaoyan; Lin, Chen; Zhou, Sunying; Su, Huimin
Abstract : An electrochemical N -acylation of carboxylic acids with amines was reported. Abstract : An electrochemical N -acylation of carboxylic acids with amines was reported. The sustainable TBAB electrocatalysis proceeded with excellent chemoselectivity and positional selectivity, and with ample scope, allowing electrochemical N -acylation under mild reaction conditions at room temperature in water. Moreover, the synthetic utility of the current method is demonstrated by the synthesis of melatonin.